The portable business writer - Murdick, William (English essentials, 1999)
This brief, inexpensive guide for business writers offers experience-based instruction as well as strong pedagogy emphasizing case studies, assignments, and models of business writing. The text covers a wide range of traditional topics, as well as important contemporary issues related to intercultural communication, writing for email and the Internet, audience, written and oral presentations, non-biased language and policy, and electronic job searches.